Spouted Bed Reactor for kinetic Measurements of Reduction of Fe2O3 in a CO2/CO Atmosphere Part I - Atmospheric Pressure Measurements and Equipment Commissioning - Fennell,PS; Zhang,Z; Hills,T; Scott,S (Chemical Engineering Research & Design, 2016)
A high pressure and high temperature spouted bed reactor, operating in fluidisation mode, has been designed and validated at low pressure for the study of gas-solid reaction kinetics. Measurements suggested the bed exhibited a fast rate of gas interchange between the bubble and particulate phases. Pressurised injection of the particles to the bottom of the bed allowed the introduction of solid reactants in a simple and controlled manner. The suitability of the reactor for the purpose of kinetic studies was demonstrated by investigation of the intrinsic kinetics of the initial stage of the reduction of Fe2O3 with CO over multiple cycles for chemical looping.Changes of pore structure over the initial cycles were found to affect the observed kinetics of the reduction. The initial intrinsic rate constant of the reduction reaction (ki) was measured by using a kinetic model which incorporated an effectiveness factor. The uncertainty arising from the measurement of particle porosity in the model was compensated for by the tortuosity factor. The average activation energy obtained for cycles three to five was 61 ± 8 kJ/mol, which is comparable with previous studies using both fluidised beds and thermogravimetry.